Efektivitas Penggunaan Media Kartu Warna Terhadap Keterampilan Menulis Pantun Siswa Sekolah Dasar - Hendra; Bahrun; Munir (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
This study aims to find out how the effectiveness of Wana Card media on students' rhyme writing skills in Indonesian language learning class V of SD Negeri Tille. This type of research is a quantitative experiment (pre-experimental). This design uses an experimental class given a learning model. After being given the treatment, a final test was given. The normality testing criteria is sig value > 0.05, the data is normally distributed, if sig < 0.05, the data is not normally distributed. From the test results, the Pretest value is 0.007 > 0.05 and the Post-test value is 0.07 > 0.05. From these tests, it can be concluded that the Pretest value is greater than 0.05 and the Post-test value is greater than 0.05. The homogeneity test results obtained Sig value α = 0.198, this means that the Sig value is greater than α (0.198 > 0.05) so that it can be concluded that the two groups are homogeneous. the hypothesis results obtained Sig (2.Tailed) = 0.000 meaning that H0 is rejected because Sig (2.Tailed) < α or (0.000 < 0.05). H1 is accepted because Sig (Tailed) > α or (0.198 > 0.05). In the T test analysis, Sig < table or (0.198 < 1.267).